The imbalance of T-cell immunoglobulin and ITIM domain and CD226 on regulatory T cell in recurrent spontaneous abortion patients. Issue 3 (30th September 2022) - Li, Cui; Ying, Chun-Mei; Duan, Zhong-Liang
Abstract : Objective: To analyze the proportion of peripheral regulatory T cells (Tregs) and the expression of the immune checkpoint molecules T-cell immunoglobulin and ITIM domain (TIGIT) and CD226 on Tregs in patients with recurrent spontaneous abortion (RSA). Methods: The proportion of CD3 + CD4 + CD25 + Foxp3 + Tregs and the expression levels of CD226 and TIGIT on Tregs in 30 normal pregnant women and 28 patients with RSA were determined via flow cytometry. Results: The proportion of Tregs in the RSA group (4.41% ± 1.54%) was significantly lower than that in the control group (5.27% ± 1.52%, P = 0.0374). Compared with the normal pregnant women, patients with RSA showed decreased TIGIT expression (54.75 ± 9.70% vs . 63.07 ± 12.48%, P = 0.0066) and increased CD226 expression on Tregs (25.59% ± 8.22% vs. 20.46% ± 6.97%, P = 0.0168). The ratio of CD226 to TIGIT in the RSA group (0.48 ± 0.19) was higher than that in the control group (0.34 ± 0.15, P = 0.0027). The proportion of TIGIT + CD226 + Tregs was significantly lower in patients with RSA (9.30% ± 4.95% vs . 13.43% ± 4.72%, P = 0.0020) than in the controls. Conclusions: Patients with RSA show a reduced proportion of Tregs and an imbalance in the expression of TIGIT and CD226 on Tregs.